2021
DOI: 10.14295/bds.2021.v24i4.2621
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of medical emergencies among dental practitioners in three Egyptian Dental Schools: A cross-sectional study

Abstract: Objectives: To evaluate the awareness of medical emergencies among dental practitioners in three dental schools. Material and methods: The study group included 384 dental practitioners, including dental staff members, post-graduate students, and dental interns. These professionals were attending three dental educational institutions in Egypt. Two of them were governmental and one was a private school. The educational model is almost the same in most Egyptian dental schools. Results: The response rate was 100%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 23 publications
1
3
3
Order By: Relevance
“…This is in line with several studies conducted by Al-Iryani et al 20 , Seemala Jyotsna et al 21 ,Gupta et al 5 ,Stafuzza et al 22 which reported significantly higher positive response rates of 82%, 61%, 69.9% %, 66% respectively. This is in contrast to other studies 10,13,16,23 where only 46.67%, 49.7%, 48.57 %,43.8%, were confident in dealing with medical emergency themselves. About 68.5% dentists have faced medical emergencies in our study.…”
Section: Discussioncontrasting
confidence: 90%
See 4 more Smart Citations
“…This is in line with several studies conducted by Al-Iryani et al 20 , Seemala Jyotsna et al 21 ,Gupta et al 5 ,Stafuzza et al 22 which reported significantly higher positive response rates of 82%, 61%, 69.9% %, 66% respectively. This is in contrast to other studies 10,13,16,23 where only 46.67%, 49.7%, 48.57 %,43.8%, were confident in dealing with medical emergency themselves. About 68.5% dentists have faced medical emergencies in our study.…”
Section: Discussioncontrasting
confidence: 90%
“…6 In our study 52.5% of practitioners noted vital signs. This is higher than a study conducted in Egypt 16 where only 41.82% obtained the vital signs of patients and also higher than a study 4 done in Saudia where 38% took it during the first visit only and 50% never took it. Conversely study by Verma et al 19 reported about 83.06% record vital signs which is significantly higher than our study.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations